(untitled) (MAUSAM, 2005)
In this paper an attempt is made to study the rainfall features associated with cyclonic systems (Depressions and cyclonic storms) during excess and deficit monsoon years over the country. It is seen statistically that there is no significant difference in number of systems that formed during excess and deficit years. In the month of May systems travel mostly towards north in excess years whereas in deficit years they travel northwest ward. In June the formation positions during excess and deficit years have no significant difference in latitude of formation. In the case of longitude, the systems in excess monsoon years form slightly to the east compared to deficit years. In September the systems not only form at lower latitudes in deficit years but also they form close to coast in deficit years than in excess years. In September number of formation of systems in excess years is more than deficit years. El- Nino is not the major factor which controls the rainfall distribution in monsoon months.